PENERAPAN GAYA SINEMATOGRAFI SLOW BURN DALAM FILM KALA MENTARI BERLALU - I Putu Suyandana; I Made Denny Chrisna Putra; Gangga Lawranta (CALACCITRA: JURNAL FILM DAN TELEVISI, 2026)
The short film Kala Mentari Berlalu addresses the issue of the sale of rice field land in Bali through a child’s perspective, employing a slow-burn cinematographic approach. This research/creative project aims to analyze the role of the Director of Photography in shaping visual rhythm, emotional resonance, and the transformation of visual style from realism to surrealism. The method applied is practice-based research, encompassing stages of conceptualization, visual design, production, and evaluation. The results indicate that the slow-burn approach is effective in gradually building the audience’s emotional engagement through long shot durations, minimalist camera movement, and subtle lighting. This film is expected to contribute to the development of fictional film cinematography practices with a reflective approach.